Noscapine hydrochloride (benzyl-isoquinoline alkaloid) effectively prevents protein denaturation through reduction of IL-6, NF-kB, COX-2, Prostaglandin-E2 in rheumatic rats - Shanila Akhter; Hafiz Muhammad Irfan; Alamgeer; Aman Ullah; Shah Jahan; Muhammad Roman; Muhammad Bilal Latif; Zaid Mustafa; Farooq M. Almutairi; Yusuf S. Althobaiti (Elsevier, 2022)
Noscapine hydrochloride (benzyl-isoquinoline antitussive alkaloid) is an opium derivative and generally used as a cough suppressant. Numerous studies on noscapine hydrochloride have reported that it has potent anti-inflammatory activity. However, the mechanisms by which it exerts an anti-inflammatory function is not well understood. Protein denaturation is the primary step that leads to the organ destruction and permanent arthritic disability. The above-mentioned facts provided the ground to plan this study using different in-vitro and in-vivo approaches. RT-qPCR and ELISA assays were used to assess the inflammatory markers related to protein denaturation in complete adjuvant persuaded rheumatism in Sprague - Dawley rats. The results were collected as paw volume and body weight changes, arthritic scoring and serum antioxidant enzymes assays. These findings demonstrated that all doses of noscapine hydrochloride (10, 20 and 40 mg/kg) studied in this study, significantly (p < 0.001) decreased the protein denaturation by preventing the increase in levels of interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), nuclear factor-kB (NF-kB), cyclooxygenase-2 (COX-2) and prostaglandin E2. Noscapine hydrochloride significantly reduced the paw volume (p < 0.001), arthritic scoring and reversed the body mass as compared to arthritic control diseased rats.